Geometry model generation for space structure / Nurul Amira Noor Khairri, Yee Hooi Min And Tey Li Sian - Noor Khairri, Nurul Amira; Yee, Hooi Min; Tey, Li Sian (Unit Penerbitan FKAPP, 2022)
Abdul Malek (2020) mentioned that TFS consists of arrangement of tensioned fabric as the main components where the fabric pattern is tensioned to a rigid structural element by mechanical means. Abdul Hadi & Yee (2016) described that TFS employed membrane supporting geometry resulting in a positive (upward) and negative (downward) curvature of the structural membrane, in which the external loads are resisted by an increase in the stress of hogging warp around one axis of the TFS and the inward forces are resisted by an increase in the stress of the sagging warps around the other. It comes in various shape and design. In this research, developing minimum surface of TFS is recommended and can be applied to TFS. Abdul Hadi (2019) stated TFS has its own basic components which consist of supporting system, seam, fabric and cables where fabric surface is the main components. The selection of the fabric type is important as details shaped. Houtman (2015) stated that the TFS can divided the fibres that make up the fabric into natural fibers and chemical fibres. The fabric surface consists of three layers, one layer of woven yarn which consisted two directions of the textile warp and weft plus two layers of coating material to protect the fabric from external destruction such as ultraviolet light (UV light) radiation degradation, rainwater, snow and atmospheric moisture. Two yarns or more can be assembled by twisting in order to obtain a thread of higher strength.